2016
DOI: 10.14814/phy2.12979
|View full text |Cite
|
Sign up to set email alerts
|

The vestibular system is critical for the changes in muscle and bone induced by hypergravity in mice

Abstract: Gravity changes concurrently affect muscle and bone as well as induce alterations in vestibular signals. However, the role of vestibular signals in the changes in muscle and bone induced by gravity changes remains unknown. We therefore investigated the effects of vestibular lesions (VL) on the changes in muscle and bone induced by 3 g hypergravity for 4 weeks in C57BL/6J mice. Quantitative computed tomography analysis revealed that hypergravity increased muscle mass surrounding the tibia and trabecular bone mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 49 publications
4
28
1
Order By: Relevance
“…Previous studies revealed that VL reduced BMD through the activation of the sympathetic nervous system in rodents [5,34]. Moreover, we reported that an adrenergic β-blocker antagonized the effects of hypergravity on skeletal muscle masses through the vestibular system in mice [8]. These findings suggest that the sympathetic nervous system is involved in the effects of the vestibular system on the cardiovascular system, bone metabolism, and skeletal muscle.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Previous studies revealed that VL reduced BMD through the activation of the sympathetic nervous system in rodents [5,34]. Moreover, we reported that an adrenergic β-blocker antagonized the effects of hypergravity on skeletal muscle masses through the vestibular system in mice [8]. These findings suggest that the sympathetic nervous system is involved in the effects of the vestibular system on the cardiovascular system, bone metabolism, and skeletal muscle.…”
Section: Discussionsupporting
confidence: 65%
“…Luxa et al reported that labyrinthectomy increased myofiber remodeling in the soleus muscle of mice [6]. We recently revealed that gravity changes affect muscle and bone through the vestibular system in mice [7,8]. Collectively, these findings suggest that the vestibular system regulates the musculoskeletal system partly through the sympathetic nervous system.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, we speculated that gravity change influences muscle-bone interactions by affecting muscle-derived factors (myokines) that link muscle to bone, which might have a partial involvement in microgravity-induced changes in muscle and bones. We investigated the hypergravity effects on muscles and bones in mice using the gondola-type centrifuge in a 3g environment with or without VL [13]. We found that a 4-week exposure to hypergravity in a 3g environment increased the anti-gravity muscle weight and fiber size, as well as the expression of muscle differentiation genes, including MyoD.…”
Section: Muscles and Bonesmentioning
confidence: 99%
“…The vestibular organ detects acceleration changes and converts them into neural signals, which are sent to the central nervous system to reflexively regulate physiological functions, including body stability (vestibulo-spinal reflex) [1], ocular movements (vestibulo-ocular reflex) [2,3], sympathetic nerve activity (vestibulo-sympathetic reflex) [4][5][6], arterial pressure (vestibulo-cardiovascular reflex), food intake [7], and body temperature [5,[8][9][10]. There have been recent reports on vestibular-related muscle and bone metabolism [11][12][13][14] and increasing attention on the various vestibular system functions. The vestibular system is known to be highly plastic, i.e., its sensitivity might be altered upon exposure to a different gravitational environment.…”
Section: Introductionmentioning
confidence: 99%